Neutrophil interaction with inflamed postcapillary venule endothelium alters annexin 1 expression - Oliani, S. M.; Paul-Clark, M. J.; Christian, H. C.; Flower, R. J.; Perretti, M. (Amer Soc Investigative Pathology, Inc, 2001)
Annexin 1 (ANX-A1) exerts antimigratory actions in several models of acute and chronic inflammation, This is related to its ability to mimic the effect of endogenous ANX-A1 that is externalized on neutrophil adhesion to the postcapillary endothelium. In the present study we monitored ANX-A1 expression and localization in intravascular and emigrated neutrophils, using a classical model of rat peritonitis, For this purpose, a pair of antibodies raised against the ANX-A1 N-terminus tie, able to recognize intact ANX-A1) or the whole protein tie, able to interact with all ANX-A1 isoforms) was used by immunofluorescence and immunocytochemistry analyses. The majority (similar to 50%) of ANX-A1 on the plasma membrane of intravascular neutrophils was intact. Extravasation into the subendothelial matrix caused loss of this pool of intact protein (to similar to6%), concomitant with an increase in total amount of the protein; only similar to 25% of the total protein was now recognized by the antibody raised against the N-terminus tie, it was intact). In the cytoplasm of these cells, ANX-A1 was predominantly associated with large vacuoles, possibly endosomes, In situ hybridization confirmed de novo synthesis of ANX-A1 in the extravasated cells. In conclusion, biochemical pathways leading to the externalization, proteolysis, and synthesis of ANX-A1 are activated during the process of neutrophil extravasation.